Versiones y usos de la historia desde el estado salvadoreño: a propósito del bicentenario (1811-2011) - Herrera Mena, Sajid Alfredo (2014)
This essay examines the construction of alternative historiographies as well as its uses and critiques to the traditional historiographies during the centenarian commemoration the so called “First Shout of Independence”, realized in El Salvador for the Secretariat of Culture of the Presidency -2011-. It focuses particularly in the program of research “Bicentenary, memory and nation”, developed for such a purpose.